The Use of Virtual Reality (VR) on English Students Speaking Skills in Educational Context: A Systematic Literature Review - Sudiana, Gede Agus; Santosa, Made Hery (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2024)
Technology has a significant impact on modern civilization and everyday life. Human existence without technology now feels incomplete, because technology has become an inseparable part of our lives. Its use significantly enhances human capabilities, especially in educational contexts. The application of technology in education is very important to prepare future generations to face a rapidly evolving technological landscape. One of the most technological advances in education is Virtual Reality (VR). Integrating VR into the classroom allows students to immerse themselves in a realistic and interactive environment where they can record and evaluate their performance, thereby can improving their fluency. Therefore, this research conducted a systematic literature review to examine the impact of VR use and the factors influencing its effectiveness, particularly on students speaking skills in educational settings. The PRISMA model was used as the method, selecting 13 studies from the initial 133 studies. The results show that VR can effectively and significantly improve students' speaking skills, influenced by various factors. Therefore, VR is a great technological tool that can be used to improve students speaking skills.